Learning numbers to10 - Sinclair, Karleen; Anderson, Greg; Heather, Warwick (Cairo Dar el farouk, 2004)
In this book , students will learn to write numbers6 to 10, and identify, count and draw groups of each number from 6 to 10
Mathematics
8 12 13
Keywords: Mathematics